Simulation of the Effect of Water-vapor Increase on Temperature in the Stratosphere - 毕云 陈月娟 周任君 易明建 邓淑梅 (Advances in atmospheric sciences, 2011)
To analyze the mechanism by which water vapor increase leads to cooling in the stratosphere, the effects of water-vapor increases on temperature in the stratosphere were simulated using the two-dimensional, interactive chemical dynamical radiative model （SOCRATES） of NCAR. The results indicate that increases in stratospheric water vapor lead to stratospheric cooling, with the extent of cooling increasing with height, and that cooling in the middle stratosphere is stronger in Arctic regions. Analysis of the radiation process showed that infrared radiative cooling by water vapor is a pivotal factor in middle-lower stratospheric cooling. However, in the upper stratosphere （above 45 km）, infrared radiation is not a factor in cooling; there, cooling is caused by the decreased solar radiative heating rate resulting from ozone decrease due to increased stratospheric water vapor. Dynamical cooling is important in the middle-upper stratosphere, and dynamical feedback to temperature change is more distinct in the Northern Hemisphere middle-high latitudes than in other regions and signiffcantly affects temperature and ozone in winter over Arctic regions. Increasing stratospheric water vapor will strengthen ozone depletion through the chemical process. However, ozone will increase in the middle stratosphere. The change in ozone due to increasing water vapor has an important effect on the stratospheric temperature change.